Structural data of thermostable 3D Ln-MOFs that based on flexible ligand of 1,3-adamantanediacetic acid - Cheng-Hui Zeng (Data in Brief, 2018)
In this data article, we present the structural and PARD data of the Ln-MOFs. Detailed structure, luminescence and sensing properties were discussed in our previous study (Zeng et al., in press) [1] The data includes the SBU structure patterns of these Ln-MOFs, thermostability of Ln-MOFs in water and also detailed structure information listed in Tables 1–8.